Method for controlling the operation of MAC layer protocols in wired networks - Kutsenko, S. O.; Voronets, V. M.; Pustovoitov, P. E. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The paper considers a method for increasing the efficiency of media access control (MAC) protocols in wired networks by dynamically controlling protocol parameters in real time. An approach is proposed that allows adaptively changing access priorities and time intervals depending on the network load and the type of transmitted data.
Keywords: MAC layer; wired networks; access control; adaptive protocol; priorities.